The perception and degree of information on sexual health among junior and high school students: a case study - Brenneisen, Icléa; Serapião, Carlos José (O Mundo da Saúde, 2007)
Many are the works and attempts to reduce the consequences of a badly advised and practiced sexuality mainly among adolescents. Many authors defend Formal Schooling as a tool for the solution of these observed problems. The proposal of developing this research concerns the collection of more information among adolescents about their knowledge about the subjects of Sexuality, Adolescence and Puberty, as well as determining the level of information their family have; identifying ways of guiding them to a better exercise of citizenship; broadening the social responsibility of adolescent students and intensifying the relevant care for their own health. A case study was done with a random sample with a group of 327 students from age ten to seventeen (n=79) and their parents (n=79), in a stratified proportional sample, at a specific private school in Joinville, Santa Catarina, Brazil. An anonymous questionnaire was used to investigate the information level – knowledge of some aspects of sexuality. This study observed the variables related to adolescents (age, sex and school grade) and their parents (age and schooling), as well as the information level of adolescents and their parents about the subjects proposed. The results, submitted to statistic analysis, showed that most adolescents did not know, for example, what the fertile period of the menstrual cycle is and also showed that they had books, magazines and newspaper, television and teachers from school as their main source of information about sex. Adolescents presented an irregular level of information about the three subjects proposed and their parents presented a regular level of information in terms of the instruments used in this research. The association of the information level of parents with age and schooling, when adjusted, did not show a significant difference. The final results obtained suggest the need of more frequent debates about sexual and reproductive heath at schools for students and their parents and teachers in order to give them subsidies sufficient for contributing to reduce doubts adolescents have.